Price Transmission Between Input and Output Markets: The Covid-19 Effect on Laying Hens’ Industry in Indonesia - Evalia, Nur Afni; Harianto; Nurmalina, Rita; Hakim, Dedi Budiman (School of Business, Bogor Agricultural University (SB-IPB), 2022)
Corn and poultry are two strategic commodities supporting food security and highly dependent on one another. This study analyses the short-term and long-term relationship between the price variables for eggs, broiler, and corn. It determines the effect of COVID-19 at the producer and consumer levels on the price of eggs in 28 provinces in Indonesia using the Panel Autoregressive Distributed Lag (PARDL) – Pooled Mean Group (PMG) approach. The PARDL estimation showed a short-term relationship between egg, broiler, and corn price variables at the producer and consumer levels, and this is shown by a significant positive and negative relationship in several provinces. There is a substitution relationship between laying hens and broiler in North Sumatra, Riau, South Sumatra, West Java, Central Java, Banten, West Nusa Tenggara, North Sulawesi, and West Papua, while the complementary relationship only occurs in Bali. In addition, the Indonesian laying hen industry should be supported by integrated policies from upstream to downstream. This is a policy of the lowest and the highest retail price and those that regulates the creation of corn supply balance inputs as the main feed for laying hens. Keywords: corn, COV-19, laying hens, PARDL, price transmission